Histomorfometria das terminações nervosas da faringe humana por imunofluorescência: um grupo controle para o estudo da apneia obstrutiva do sono - Dantas, Guilherme Leal (2018)
Obstructive sleep apnea is a disorder characterized by recurring collapses of the pharyngeal region during sleep, resulting in reduced oxygen saturation and a high risk of cardiovascular diseases. The physiopathological mechanism remains unclear. Evidence suggests that changes in the proprioceptive sensory innervation of the pharynx may contribute to emergence of the disease. The primary aim of this study is to investigate the nerve ending morphology of palatoglossus, palatopharyngeal and superior pharyngeal constrictor muscles, and compare the nerve density of these muscles. Specimens were collected in vivo during palatine tonsillectomy in patients with normal sensory function and no obstructive sleep apnea. Nerve ending histomorphometry was assessed using immunofluorescence and hematoxylin-eosin staining. Muscle spindles were observed in the palatoglossus muscle. Free and complex nerve endings were identified in the three muscles under study, including Meissner, Golgi and Ruffini formations, in addition to spiral-wharves nerve structures in the palatoglossus and superior pharyngeal constrictor muscles. The average density of pharyngeal superior constrictor muscle nerve fibers was higher than in the palatopharyngeal muscle, which, in turn, was greater than the average of the palatoglossus muscle. The study of proprioceptive innervation of the pharynx in a control group is relevant for future research involving the neurogenic hypothesis pathogenesis of obstructive sleep apnea. Keywords: Obstructive sleep apnea. Pharynx. Pharyngeal muscles. Nerve endings. Immunofluorescence.